Studies about Abai's «Masgut» poem in China. - Mukametkhanuly., N.; Dalelgazy., T. (Journal of Oriental Studies, 2016)
The article is dealing with the studies of Hu Huanzhang (Qabai) about poem «Masgut», one of Abai's original three poems. Forthermore analyzing works of other chinese translators about the poem.